X^2 - 5x - 6

x^2 - 6x + x -6

x(x-6)+1(x-6)

(x+1)(x-6)

x^2 - 6x + x -6

x(x-6)+1(x-6)

(x+1)(x-6)

X^2 - 5x - 6

x^2 - 6x + x -6

x(x-6)+1(x-6)

(x+1)(x-6)

x^2 - 6x + x -6

x(x-6)+1(x-6)

(x+1)(x-6)

Factor: X^2+5x-6

In the quadratic expression, you first look at the coefficient of x^{2} and the constant (that is, the coefficient of x^{0}). The signs of these will tell you what the signs of the factors need to be. In this case the coefficient of x^{2} is positive (+1), so both factors will have (+1x) as one of the terms. The sign of the coefficient of x^{0} is negative, so one of the factors will be (x-something) and the other will be (x+something), like this: (x-a)(x+b).

If we multiply out what we just wrote, it will help us figure out what a and b need to be.

(x-a)(x+b) = x^{2} + x(b-a) - ab.

This tells us that the two factors of -6 need to add to get -5. Let's look at the possibilities:

-6 = -1*6, sum of factors = +5

-6 = -2*3, sum of factors = 1

-6 = -3*2, sum of factors = -1

-6 = -6*1, sum of factors = -5. It looks like this might do it.

x^{2} - 5x - 6 = (x - 6)(x + 1)

_____

Now that you have multiplied out (x - a)(x + b), you know the coefficient of x^{1} in a quadratic is the sum of the factors of the coefficient of x^{0}. Because you know this, you can "cut to the chase" when you do future problems.

If the coefficient of x^{2} is not 1, then you have to work the factors of that coefficient into the mix. You can do the same sort of "multiply it out and see what you get" exercise we did above to give you a clue where to start.

If we multiply out what we just wrote, it will help us figure out what a and b need to be.

(x-a)(x+b) = x

This tells us that the two factors of -6 need to add to get -5. Let's look at the possibilities:

-6 = -1*6, sum of factors = +5

-6 = -2*3, sum of factors = 1

-6 = -3*2, sum of factors = -1

-6 = -6*1, sum of factors = -5. It looks like this might do it.

x

_____

Now that you have multiplied out (x - a)(x + b), you know the coefficient of x

If the coefficient of x

Use diamonds and dust. It looks like an ╳, so the top portion would be -6 while vertically from the top would be -5. So the two spaces on the sides when multiplied together equals -6 but when added equals -5.

So the factor would be"

(x-1)(x+1)

and if you want to find the zeroes set the factors to 0.

X-1=0 x+1=0

add 1, subract one.

So the zeroes would be x= -1,1

So the factor would be"

(x-1)(x+1)

and if you want to find the zeroes set the factors to 0.

X-1=0 x+1=0

add 1, subract one.

So the zeroes would be x= -1,1

(x+2)(x+3)

Given: X^{2} - 5x - 6

Answer: (x+1) (x-6)

I really don't know how to explain it... So yeah, I hope this help.

Answer: (x+1) (x-6)

I really don't know how to explain it... So yeah, I hope this help.

Didn't find the answer you were looking for?